(untitled) (Boletín de Investigaciones Marinas y Costeras, 2016)
Fishes and macroinvertebrates associated to two types of articial habitats deployed in Taganga Bay were assessed by stationary visual census to compare these assemblages. Forty-one species of shes and nine macroinvertebrates were observed in eleven visual censuses. The distribution patterns depicted in abundance and richness between the two types of habitats used (concrete blocks vs. articial shelters), were a possible response to dissimilarities in their location and number of visual census. A relative high sh richness and diversity were found in these articial habitats, in comparison to other articial structures in Colombia, probably owing to their proximity with heterogeneous natural habitats. The use of complex articial habitats could have potential useful to conserve, restore and manage some marine resources supported in planned researches in this area.